Moderate Fiqh in The Perspective of Islamic Boarding School Students: (The Study of Mahasantri Ma`Had Aly Situbondo) - Muzakki, Ahmad (STAI Syaichona Moh. Cholil Bangkalan, 2023)
Moderation in fiqh issues is one of the things that must be developed because it has a comprehensive character. This study aims to determine the moderate fiqh reasoning of students of Mahad Aly Salafiyah Syafi`iyyah Situbondo in building religious moderation. This research uses a literature review using the method of traditional review. The type of data used is secondary data, namely data obtained from library materials by reading and studying the works of Ma`had Aly Salafiyah Syafi`iyyah Situbondo students with the titles People's Fiqh, Reality Fiqh, Building Central Islam, and Progressive Fiqh. Based on the discussion and analysis that has been done, it can be concluded that Ma`had Aly Salafiyah Syafi`iyyah Situbondo is an educational institution that concentrates on fiqh and ushul fiqh studies. Through moderate fiqh reasoning, several works of thought were born in book form: Reality Fiqh, People's Fiqh, Building Central Islam, and Progressive Fiqh. In these works, efforts are made to build religious moderation by broadening the horizons of fiqh thinking with the study of fiqh from the four schools of thought combined with ushul fiqh and fiqh rules, combining text and reality, and avoiding fanaticism within schools of thought to give birth to solutive thinking, tolerance, unity, harmony, and awareness in the state and religious life.